The Development of a Web-Based Tobacco Tracker Tool to Crowdsource Campus Environmental Reports for Smoke and Tobacco-Free College Policies: Mixed Methods Study - Sabrina F Loureiro; Kim Pulvers; Melissa M Gosdin; Keavagh Clift; Myra Rice; Elisa K Tong (JMIR Publications, 2021)
BackgroundCollege campuses in the United States have begun implementing smoke and tobacco-free policies to discourage the use of tobacco. Smoke and tobacco-free policies, however, are contingent upon effective policy enforcement. ObjectiveThis study aimed to develop an empirically derived web-based tracking tool (Tracker) for crowdsourcing campus environmental reports of tobacco use and waste to support smoke and tobacco-free college policies. MethodsAn exploratory sequential mixed methods approach was utilized to inform the development and evaluation of Tracker. In October 2018, three focus groups across 2 California universities were conducted and themes were analyzed, guiding Tracker development. After 1 year of implementation, users were asked in April 2020 to complete a survey about their experience. ResultsIn the focus groups, two major themes emerged: barriers and facilitators to tool utilization. Further Tracker development was guided by focus group input to address these barriers (eg, information, policing, and logistical concerns) and facilitators (eg, environmental motivators and positive reinforcement). Amongst 1163 Tracker reports, those who completed the user survey (n=316) reported that the top motivations for using the tool had been having a cleaner environment (212/316, 79%) and health concerns (185/316, 69%). ConclusionsEnvironmental concerns, a motivator that emerged in focus groups, shaped Tracker's development and was cited by the majority of users surveyed as a top motivator for utilization.